Differentiated inhabitation of ‘auteur architecture’: photographing Álvaro Siza’s Bouça housing estate - Machado, Marta (2025)
This paper explores the different ways residents of famous buildings experience the architecture they live in. We aim at an architectural photography that seeks to portray architecture not as a visual phenomenon but rather a lived one. We have photographed residents of the Bouça housing estate in Porto, Portugal, designed in the 1970s by Pritzker Prize winning Portuguesearchitect Álvaro Siza to house the urban poor after the 1974 revolution. The estate has since become an architectural icon and is currently undergoing gentrification by architects, designers and artists who are drawn to the appeal of ‘auteur architecture’. The differences in inhabitation between the original residents and the recent ones pertain to a complex yet dualistic stance between two distinct social classes on what architecture is and what it means, one that also raises the issue of housing for the urban poor becoming fashionable. We read such tensions while tracing back to Siza’s early belief in a classless society, which later evolved into the belief in an ‘interclassist city’. Cover image: Costa et al., “Inhabiting Auteur Architecture.”